2017
DOI: 10.1111/1471-0528.14759
|View full text |Cite
|
Sign up to set email alerts
|

Fetal head position and perineal distension associated with the use of the BD Odon Device™ in operative vaginal birth: a simulation study

Abstract: Objective To investigate (1) the placement of the BD Odon Device on the model fetal head and (2) perineal distention during simulated operative vaginal births conducted with the BD Odon Device.Design Observational simulation study.Setting North Bristol NHS Trust, UK.Population or sample Four hundred and forty simulated operative vaginal births.Methods Three bespoke fetal mannequins were developed to represent (1) bi-parietal diameter of the 50th centile at term, (2) bi-parietal diameter at the 5th centile at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The BD Odon Device is the first new device for AVB since the introduction of ventouse into clinical practice in the 1950s [16]. Extensive pre-clinical simulation testing has suggested that it is not likely to generate additional pressure over the fetal head compared with current instruments [9, 17], is not likely to generate clinically significant levels of neonatal hypoxia if misplaced over the fetal carotid arteries [10], and is not likely to be associated with unsafe patterns of use by the target user population [12]. We believe that it is therefore reasonable to proceed to a clinical feasibility study of the device, and, if positive, a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…The BD Odon Device is the first new device for AVB since the introduction of ventouse into clinical practice in the 1950s [16]. Extensive pre-clinical simulation testing has suggested that it is not likely to generate additional pressure over the fetal head compared with current instruments [9, 17], is not likely to generate clinically significant levels of neonatal hypoxia if misplaced over the fetal carotid arteries [10], and is not likely to be associated with unsafe patterns of use by the target user population [12]. We believe that it is therefore reasonable to proceed to a clinical feasibility study of the device, and, if positive, a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of negative pressure on the fetal head, the mechanism of action of the ventouse, is designed to eliminate vacuum-associated haematoma and haemorrhage. These contentions have been supported in pre-clinical simulation studies [ 8 10 ].
Fig.
…”
Section: Introductionmentioning
confidence: 87%
“…17 The Odon Device (figure 1) was invented by an Argentinean Car Mechanic and then further developed by a multiprofessional team of doctors, midwives and engineers as an alternative device. [18][19][20][21][22] The device consists of a plastic applicator and polyethylene sleeve. The sleeve is placed over the fetal head and contains a circumferential air chamber that is inflated, providing purchase for the operator to apply traction.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%